Establishment and investigation of a cultivation process for the production of a recombinant antimicrobial peptide in Escherichia coli using design of experiments - Burcin Boran (2024)
The discovery and research of antibiotics opened up a new application area of medicine and a new way of disease treatment. However, a relative quick stagnation of development of new antibiotics turned out. Alongside drug pollution of the environment gained much more attention caused by incorrect disposal by humans as well as using antibiotics for livestock farming. Another severe risk for humans is the development of resistance of microorganisms to antibiotics. Antimicrobial peptides (AMPs) can overcome these drawbacks of antibiotics. AMPs are natural occurring peptides obtained from different natural sources and from prokaryotic and eukaryotic organisms. Research and development is increasing because AMPs can be used as alternatives for antibiotics. They contain a wide spectrum of activity against different kind of microorganisms as well as in the fight against cancer. In addition to the development of new AMPs and their possible activities, a process for production needs to be developed for already known AMPs. In this work a recombinant protein production is established using E. coli as host system. At beginning the establishment of the preculture, a fed-batch process and a method for analyzing the outcome is established. First cultivation processes were developed in the bioreactor system Biostat® Bplus. Afterwards,a fed-batch process is investigated by creating a DOE. Screening experiments were carried out in Biostat® CTA and CTB. As factors tFB, tP and μP are chosen. With a fed-batch time of tFB = 20 h, a production time of tP = 5 h and a growth rate of μP = 0.05 h-1 a product yield of 27.01 g g-1 cells is obtained.